On Sperner \(Γ\)-(semi)hypergroups - Iranmanesh, M.; Jafarpour, M.; Aghabozorgi, H. (Communications in Mathematics and Applications, 2017)
In this paper first we use the notion of Sperner family and we introduce some classes of \(Γ\)-(semi)hypergroups that we call them weak Sperner \(Γ\)-(semi)hypergroups and Sperner \(Γ\)-(semi)hypergroups. Then we introduce the class of complete \(Γ\)-(semi)hypergroups as a generalization of the class of complete semihypergroups and we show that every complete \(Γ\)-(semi)hypergroups is a Sperner \(Γ\)-(semi)hypergroups. Finally the class of complementable \(Γ\)-(semi)hypergroups is investigated.